Theoretical Aspects of Collective Decision Making - Survey of the Economic Literature - Stanek, Piotr (Comparative Economic Research. Central and Eastern Europe, 2013)
The article aims at surveying the economic literature related to collective decision making. In order to do so it proposes a coherent framework allowing for a structured analysis of the factors influencing the works of a committee. These factors are divided into external ( shaped outside of the committee e.g. by law) and internal ones (related to the composition of the committee and interactions between its members). The survey of the general economic literature related to collective decision making presented within the proposed framework yields interesting suggestions for further research, including the consequences for the shape of monetary policy committees.